1917 N.H. Laws 727-28, § 2 - (:unkn) unknown (My University, 1917)
An Act for the Regulation of the Sale and Use of Explosives and Firearms, ch. 185, § 2: No such licensed person shall sell or deliver firearms to any person not a citizen of the United States, unless he shall have legally declared his intention of becoming a citizen, or any such explosive material or compound to any person, except upon presentation of a permit such as is hereinafter provided for, nor unless satisfied that the same is to be used for a lawful purpose.
Keywords: TRANSFER - DANGEROUS PERSONS